November 2020 Placement Ads (The Accounting Review, 2020)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for updated, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.KENT STATE UNIVERSITY, Department of Accounting invites applications for a tenure-track position at the Assistant Professor level beginning Fall 2021. Experienced assistant professors are encouraged to apply. We are primarily interested in candidates who have research and teaching interests in auditing and/or financial accounting. Candidates must have completed or nearly completed a doctoral degree in Accounting. Research will be expected in top and high-quality academic journals. Professional certification is desirable. Participation in the Ph.D. program will be part of the faculty member's responsibilities. Review of applications will begin immediately and continue until the position is filled. Please submit a cover letter, curriculum vitae, at least one working paper, evidence of teaching effectiveness, and the contact information of three references. Applicants should apply online at: https://jobslist.kent.edu/cw/en-us/listing/?jobnotfound=true and submit the application materials described above for job number 991450. AA/EOETHE UNIVERSITY OF NORTH CAROLINA AT CHARLOTTE, Belk College of Business, Turner School of Accountancy invites applications for a Director/Department Chair to begin in August 2021. The new Director will be hired with tenure at the rank of Professor (preferred) or Associate Professor. The primary duties of the Director include internal administration of the Turner School and external engagement with industry partners and alumni. The Turner School is named for Mr. Thomas C. Turner, who helped establish the accounting department at UNC Charlotte, and is funded with an endowment of more than $4 million to support students and faculty, with additional commitments already made. Applications must be made electronically at: https://jobs.uncc.edu/ or directly at: https://jobs.uncc.edu/postings/32402/./ A more detailed description of the job duties and required application materials are available at the posting. For more information, email Dr. Artie Zillante, chair of the search committee, at artie.zillante@uncc.edu.SANTA CLARA UNIVERSITY, Department of Accounting invites applications for a tenure-track position beginning Fall 2021. The position is for the rank of Assistant Professor, although candidates with exceptional scholarly achievement may be considered for higher ranks. We encourage applications from candidates in all areas of research and teaching, especially those interested in teaching auditing or advanced accounting. Candidates should have completed or nearly completed their Ph.D.s and must demonstrate capacity to undertake scholarly research publishable in leading journals and to provide quality teaching. Please submit a cover letter, cv, sample of research, evidence of teaching effectiveness, and three letters of recommendation using the university's online application process at: https://wd1.myworkdaysite.com/recruiting/scu/scu/job/Santa-Clara-CA/Tenure-Track-Position-in-Accounting_R863/. Applications will be accepted and reviewed until the position is filled. SCU is a private Jesuit university located in Silicon Valley. We provide housing subsidies and competitive summer research support. SCU is an EEO/AA employer.GEORGIA COLLEGE AND STATE UNIVERSITY, J. Whitney Bunting College of Business invites applications for the position of Department Chair of Accounting beginning August 2021. Disciplinary background in either Accounting or Business Law will be considered. Working collaboratively with the faculty in the Department of Accounting, the Chair is responsible for providing administrative leadership for the department and for implementing the Department's and College's goals, giving special attention to the objectives for the academic programs of the Department including courses and faculty in Business Law and Ethics. The Chair also maintains and enhances the connection between the Department of Accounting and the Accounting business community to establish the vision and direction for the Accounting and Business Law curriculum. The Chair serves on the College's Leadership Team and reports directly to the Dean of the J. Whitney Bunting College of Business. The Department of Accounting has approximately 225 students with 13 FTE faculty and staff offering both a B.B.A. in Accounting and a Master of Accountancy degree program. Please submit application to: https://www.gcsujobs.com/postings/8236BEMIDJI STATE UNIVERSITY (BSU) invites qualified applicants to join our team as an Assistant or Associate Professor of Accounting. BSU's vision is to educate people to lead inspired lives. To accomplish this, the University prioritizes creating a culture in which diversity is embraced and all people are safe, welcome, and validated. BSU also prioritizes increasing engagement with Indigenous communities to become a destination university. For details visit: https://bemidjistate.peopleadmin.com/MICHIGAN TECHNOLOGICAL UNIVERSITY, College of Business invites applications for a tenure-track Assistant Professor of Accounting starting August 2021. MTU has an undergraduate and graduate program in Accounting, and has recently added concentration and certificate programs in Accounting Data Analytics and Forensic Examination. The successful candidate will be expected to develop and/or continue a vigorous, nationally visible research program, engage in quality teaching in both the undergraduate and graduate accounting degree programs, and provide service to the department and university. The prospective candidate will support a student-centric, learner-oriented, experiential approach to instruction. Applications must be submitted online at: https://www.employment.mtu.edu/cw/en-us/listing/ and include the following: (1) a letter of application describing qualifications for the position and (2) a current curriculum vitae. Applicants will be asked to provide contact information for three recommendation providers. The position will remain open until filled.CATHOLIC CHARITIES OF SANTA ROSA is currently looking for the right person to join our accounting team as the Agency Controller. Our ideal candidate will be a CPA, have experience working in a non-profit environment, be not only a leader, but also work well as part of a team, and be passionate about our mission of serving the most vulnerable in our community. To apply or for more information, please go to: https://secure2.saashr.com/ta/i.CCH.careers?CareersSearchGRACELAND UNIVERSITY, C. H. Sandage School of Business in Lamoni, Iowa is seeking an Assistant Professor of Accounting to begin January 2021. This may be a Visiting Professor or a full-time, nine-month, tenure-track position, depending on the candidate's experience level, education, and overall fit for the position. Candidates should possess at least a master's degree in accounting and the credentials to teach business administration courses or a master's degree in business administration and the credentials to teach accounting courses. Strong preference will be given to candidates with a PhD in accounting or business administration and an advanced degree or experience in business analytics. Teaching responsibilities include a 4/4 teaching load consisting of a wide range of accounting and business courses, including Financial, Managerial, Intermediate, Tax, Cost, and Auditing, with exact course assignments determined by the area of specialty of the candidate. Qualified applicants should submit a letter of application, cv, evidence of teaching effectiveness, and contact information for at least three professional references (one reference must address teaching experience and abilities) to: Dr. Jeffery W. McElroy, Dean, C. H. Sandage School of Business, at: jeffery.mcelroy@graceland.edu. For more, see: https://www.graceland.edu/employment/news/1692787/assistant-professor-of-accounting